2012
DOI: 10.1093/infdis/jis500
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactive and Vaccine-Induced Antibody to an Emerging Swine-Origin Variant of Influenza A Virus Subtype H3N2 (H3N2v)

Abstract: NCT01140009 and NCT01368796.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
80
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 29 publications
15
80
0
Order By: Relevance
“…1 Our age-based serosurvey indicated that cross-reactive antibodies to novel H3N2v were undetectable or present at very low levels in sera from young schoolaged children. These findings are consistent with results of previous population serosurveys (12)(13)(14). Thus, individuals born after 1996 have a higher risk of H3N2v infection and could become mediators to the spread of the H3N2v virus within a community.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…1 Our age-based serosurvey indicated that cross-reactive antibodies to novel H3N2v were undetectable or present at very low levels in sera from young schoolaged children. These findings are consistent with results of previous population serosurveys (12)(13)(14). Thus, individuals born after 1996 have a higher risk of H3N2v infection and could become mediators to the spread of the H3N2v virus within a community.…”
supporting
confidence: 93%
“…The high seroprevalence of the H3N2v virus in older teenagers and young adults (born between 1996 and 1971; age, 15-39 years) was probably due to the exposure to seasonal H3N2 viruses circulating during their childhoods as described previously (12)(13)(14). In fact, the HA gene of H3N2v is considered to be descended from seasonal H3N2 viruses that were circulating in the 1990s (15).…”
supporting
confidence: 53%
“…original antigenic sin). Annual vaccination, as opposed to less frequent infection exposure, may hasten such 'sinful' antibody refocusing toward prior versus evolved epitopes, preferentially selecting for cross-reactive but non-neutralizing memory responses [44][45][46][47]. In the context of pre-existing antibody, immune complex formation and Fc-receptor activation can lead to suppression of B cell responses to subsequent influenza vaccination [48].…”
Section: Possible Immune Mechanisms For Repeated Vaccination Effectsmentioning
confidence: 99%
“…Only modest increases in crossreactive antibodies to H3N2v viruses were detected in individuals of any age who received seasonal trivalent inactivated vaccine (CDC, 2012;Skowroski et al, 2012). The HA of H3N2v has an amino acid homology of 89 % compared with current human seasonal influenza H3N2 vaccine virus (A/Perth/16/2009) (Lindstrom et al, 2012 Evidence from serological studies indicates that young children can be expected to have little immunity to these H3N2v viruses (CDC, 2012d;Skowronski et al, 2012;Waalen et al, 2012). However there is evidence to suggest that young adults, aged 20 to 40 years, may have cross-reactive antibodies to H3N2v, most likely due to exposure to human H3N2 viruses that circulated in the early to mid-1990s.…”
Section: Cross-immunity In Humansmentioning
confidence: 99%
“…Regarding adaptive immune response, as already described in Chapter 8 (Section 8.4), there is an age-related presence of cross-protective antibodies against H3N2v in the human population, with children < 10 years old being most susceptible and, to a lesser extent, adults > 50 years old. Less vulnerable are people aged 20-40 years (CDC, 2012d; Skowronski et al, 2012;Waalen et al, 2012). Therefore, this may represent a barrier to the human-tohuman transmission of this virus.…”
Section: Replication and Releasementioning
confidence: 99%